"A Learning Process Versus a Moment": Engaging Black Male Teacher Education Candidates in Culturally Sustaining Pedagogy at Jackson State University. Issue 2 (10th November 2020) - Ginsberg, Alice; Gasman, Marybeth; Castro Samayoa, Andrés
Abstract: This qualitative case study provides a deep dive into a teacher education program at Jackson State University, a Historically Black University (i.e. HBCU) located in Mississippi that is intentionally preparing Black men teacher candidates to successfully support the academic achievement of students in culturally diverse, low-income, and underserved schools.